Imaginaries of corruption in Perder es cuestión de método [Losing is a Matter of Method] by Santiago Gamboa - Avilés Arenas, Leonor (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The article interrogates the meaning of imaginaries of corruption in the novel Perder es cuestión de método (1997) by Santiago Gamboa. For this, the imaginary is understood as a relational assembly of dilemmatic images; while corruption is defined, based on the content of the work, as an illegal and egocentric action that places self interest above the interests of the political majority. The semiotic analysis of statements and figures will be used to determine how imaginaries of corruption are represented in Gamboa’s novel. These imaginaries are classified according to the stratum in which they manifest themselves: physiological, psychological and social. The analysis also focuses on the fact that these strata are interdependent and work as parts of a complex phenomenon; contributing to the organicity of the narrative.